Pillage / 1. - Skye, Obert (Shadow Mountain, 2008)
Upon his mother's death, fifteen-year-old Beck Phillips is sent to live with an eccentric uncle he had never met in a remote manor house, where he learns that his family suffers from a curse that allows him to make plants grow on command and dragon eggs hatch.